The Hippodrome of Gerasa : a provincial Roman circus - Ostrasz, Antoni A. 1929-1996, (Archaeopress Archaeology, 2020)
This book presents the study of Roman circuses and the complex fieldwork for the restoration of the Jarash Hippodrome, a work in progress abruptly ended by the untimely death of Antoni A. Ostrasz in 1996. It aims to provide researchers as well as restorers of ancient monuments with unparalleled insights of architectural studies for anastyloses.